Lhx5 controls mamillary differentiation in the developing hypothalamus of the mouse - Heide, Michael; Zhang, Yuanfeng; Zhou, Xunlei; Zhao, Tianyu; Miquelajauregui, Amaya; Varela-Echavarria, Alfredo; Alvarez-Bolado, Gonzalo (Frontiers in neuroanatomy, 2015)
Acquisition of specific neuronal identity by individual brain nuclei is a key step in brain development. However, how the mechanisms that confer neuronal identity are integrated with upstream regional specification networks is still mysterious. Expression of Sonic hedgehog (Shh), is required for hypothalamic specification and is later downregulated by Tbx3 to allow for the differentiation of the tubero-mamillary region. In this region, the mamillary body (MBO), is a large neuronal aggregate essential for memory formation. To clarify how MBO identity is acquired after regional specification, we investigated Lhx5, a transcription factor with restricted MBO expression. We first generated a hypomorph allele of Lhx5—in homozygotes, the MBO disappears after initial specification. Intriguingly, in these mutants, Tbx3 was downregulated and the Shh expression domain abnormally extended. Microarray analysis and chromatin immunoprecipitation indicated that Lhx5 appears to be involved in Shh downregulation through Tbx3 and activates several MBO-specific regulator and effector genes. Finally, by tracing the caudal hypothalamic cell lineage we show that, in the Lhx5 mutant, at least some MBO cells are present but lack characteristic marker expression. Our work shows how the Lhx5 locus contributes to integrate regional specification pathways with downstream acquisition of neuronal identity in the MBO.